Ojcostwo w doświadczeniach niepełnoletnich chłopców - Ratajczak, Łukasz P. (Wydawnictwo Naukowe UAM, 2016)
The theoretical analysis and research presented in this book deals with the issue of premature fatherhood of underage boys. Teenage fatherhood can be analysed as a multidimensional phenomenon since the experiences that are related to it can impact (directly or indirectly) on various aspects of teenagers’ life. Bearing in mind the life stage at which this phenomenon occurs, it can be considered a premature experience. It is also reasonable to assume that this experience will have various consequences, not only in the life of young fathers, but also in that of their children and (female) partners. Preventive activities and support schemes related to underage boys’ parenthood are in need of a diagnosis related to this phenomenon. Undertaking research that would lead to such a diagnosis seems both entirely reasonable and also important for society. Research carried out so far (using the biographical (-narrative) interview method with a sample of 40 respondents) provide an insight into who the premature fathers and their partners (the mothers of their children) are, and also what their (life) situation is at the time of conceiving the child. Above all, this research made it possible to find out in broad terms just what the boys experience in relation to their fatherhood. In view of the social significance of this issue, these research findings might serve as the basis for developing preventive programmes, but also those targeting directly teenage fathers, thus providing them with help and support in taking on and performing the role of father. The knowledge that stems from their narratives can also become an important addition to the social debate on the issue of teenage fatherhood.

W książce podjęto ważny ze społecznego i indywidualnego punktu widzenia problemu, jakim jest ojcostwo niepełnoletnich osób. Przedmiotem rozważań teoretycznych i analiz empirycznych jest problematyka rodzicielstwa niepełnoletnich chłopców, a także ich doświadczenia związane z (przed)wczesnym podjęciem i pełnieniem roli rodzicielskiej. W pierwszej części przedstawiono rozważania teoretyczne stanowiące przegląd literatury przedmiotu. Empiryczną część pracy autor rozpoczyna od prezentacji założeń badawczych, następnie przedstawia analizy uzyskanych wyniki badań, porządkując je wg następujących obszarów problemowych: sytuacji życiowej i zachowań niepełnoletnich chłopców przed uzyskaniem informacji o ciąży partnerki; doświadczeń związanych z uzyskaniem przez nastoletnich chłopców informacji o poczęciu dziecka i doświadczeń niepełnoletnich ojców związanych z urodzeniem się dziecka oraz podjęciem i pełnieniem przez nich roli ojca. Analizę tę dopełniono fragmentami narracji niepełnoletnich ojców.
Fatherhood as experienced by underage boys
Keywords: rola ojca; niepełnoletni ojcowie; rola społeczna; ojcostwo